Pachychoroid spectrum disease and choriocapillary flow analysis in patients with Cushing disease: an optical coherence tomography angiography study - Lassandro, Nicola Vito; Nicolai, Michele; Arnaldi, Giorgio; Franceschi, Alessandro; Pelliccioni, Paolo; Cantini, Luca; Gesuita, Rosaria; Faragalli, Andrea; Mariotti, Cesare (Graefe's archive for clinical and experimental ophthalmology, 2022)
Purpose To investigate the presence of pachychoroid spectrum disease (PSD) in patients with Cushing disease (CD) and to evaluate subfoveal choroidal thickness (SFCT) and choriocapillary flow using spectral domain OCT (SD-OCT) with the enhanced depth imaging (EDI) and optical coherence tomography angiography (OCT-A). Methods Thirty-two patients with CD and 32 age- and sex-matched healthy volunteers were enrolled in this observational study. All participants had a complete ophthalmic examination including SD-OCT with EDI and OCT-A, and were subjected to the Perceived Stress Scale test (PSS). All patients with CD had hormone test including 24-h urinary-free cortisol (UFC) and plasma adrenocorticotropic hormone (ACTH). We compared SFCT and choriocapillary vessel density (CVD) between the two groups and evaluated the presence of PSD. We investigated the association of hormone level, SFTC, CVD with the presence of CD; the association between the hormone level, SFTC, CVD, the CD disease activity, and duration with the presence of PSD in CD patients; and the association between SFTC and CVD with the hormone level, the CD disease activity, and duration in CD patients. Results Higher values of SFCT and CVD were associated with CD ( β : 0.028, 95% CI: 0.014; 0.041; β : 0.912, 95%CI: 0.205; 1.62, respectively). Twelve patients with CD (37.5%) reported a PSD in at least one eye, whereas no subject was found in control group ( p < 0.001); in particular, 11 CD patients (34%) presented pachychoroid pigment epitheliopathy (PPE) and 1 CD patient (3%) presented polypoidal choroidal vasculopathy/aneurysmal type 1 neovascularization (PCV/AT1). In patients with CD, a significant positive association between SFCT and PSD was found ( β : 0.010, 95% CI 0.001; 0.019). Conclusion A chronic state of hypercortisolism may have direct implications on the choroid. Patients with CD had higher SFCT values and a significant change in the choriocapillary flow compared to healthy controls. Moreover, PSD was observed only in CD patients.